Postharvest chilling diminishes melon flavor via effects on volatile acetate ester biosynthesis - Zhang, Huijun; Zhu, Xiuxiu; Xu, Runzhe; Yuan, Yushu; Abugu, Modesta N.; Yan, Congsheng; Tieman, Denise; Li, Xiang (Frontiers in Plant Science, 2023)
In postharvest handling systems, refrigeration can extend fruit shelf life and delay decay via slowing ripening progress; however, it selectively alters the biosynthesis of flavor-associated volatile organic compounds (VOCs), which results in reduced flavor quality. Volatile esters are major contributors to melon fruit flavor. The more esters, the more consumers enjoy the melon fruit. However, the effects of chilling on melon flavor and volatiles associated with consumer liking are yet to be fully understood. In the present study, consumer sensory evaluation showed that chilling changed the perception of melon fruit. Total ester content was lower after chilling, particularly volatile acetate esters (VAEs). Transcriptomic analysis revealed that transcript abundance of multiple flavor-associated genes in fatty acid and amino acid pathways was reduced after chilling. Additionally, expression levels of the transcription factors (TFs), such as NOR, MYB, and AP2/ERF, also were substantially downregulated, which likely altered the transcript levels of ester-associated pathway genes during cold storage. VAE content and expression of some key genes recover after transfer to room temperature. Therefore, chilling-induced changes of VAE profiles were consistent with expression patterns of some pathway genes that encode specific fatty acid- and amino acid-mobilizing enzymes as well as TFs involved in fruit ripening, metabolic regulation, and hormone signaling.